Ethoxy Carboxylate Extended Surfactant: Surface Charge of Surfactant‐Modified Alumina, Adsolubilization and Solubilization of Phenylethanol and Styrene. Issue 3 (29th September 2012) - Arpornpong, Noulkamol; Lewlomphaisan, Jirapat; Charoensaeng, Ampira; Sabatini, David A.; Khaodhiar, Sutha
Abstract: Adsolubilization of contaminants by surfactant‐modified material is an important phenomenon for surfactant‐based environmental technologies. Recently, extended surfactants have been shown to enhance the adsolubilization capacity of organic solutes. In this study, two extended surfactants (ethoxy propoxylated carboxylate extended surfactant—C16PO4EO5C and propoxylate extended sulfate surfactant—C16PO4S) were selected for modifying positively charged alumina surfaces with the aim of enhancing adsolubilization of organic solutes with varying degrees of polarity (phenanthrene, styrene, and phenylethanol). The nature of the charged surface as a function of extended surfactant adsorption was evaluated through the zeta potential measurements. The results showed that at maximum bilayer coverage, the zeta potential of the alumina surface remained constant and was oppositely charged (negative) to the unmodified alumina (positive). Zeta potential measurements showed that the adsorbed bilayer of carboxylate‐based extended surfactant produced more negatively charged surface. Surfactant desorption results showed that the surfactant‐modified surface retained their negatively charge, albeit reduced, indicating that partial desorption occurred but not to the point that the positively charged alumina surface was realized. The adsolubilization results suggest a benefit of the ethoxy groups in adsolubilizing the polar phenylethanol in the palisade layer.